Statistical analysis methods for transient flows – the dam-break case. Issue 5 (3rd September 2019) - Aleixo, Rui; Soares-Frazão, Sandra; Zech, Yves
ABSTRACT: Transient flows differ from steady flows in the sense that their dynamic variables, e.g. velocity, change with time. This imposes several constraints both on the measurement techniques to use as well on the data processing. The dam-break flow, as an example of severe transient flow, is used in this paper as test case for the application of different statistical methods identified in the literature: the common statistical tools (e.g. time average, standard deviation), the application of a Fourier-series-based method and the ensemble statistics approach. Data were collected using a fast acquisition camera and particle image velocimetry was used to obtain quantitative information about the velocity field of a set of seven dam-break flows. From the analysis made in this paper it was possible to identify in which conditions each statistical method can be applied to the dam-break flow.